Recent advances in natural polysaccharides-based controlled release nanosystems for anti-cancer phototherapy. (1st February 2023) - Xu, Haiting; Nie, Wenbiao; Dai, Linxin; Luo, Ruifeng; Lin, Dasheng; Zhang, Minyue; Zhang, Jinming; Gao, Fei
Abstract: Phototherapy, which relies on light to trigger phototherapeutic agents (PAs) to generate cytotoxic reactive oxygen species or hyperthermia, has received much attention in cancer treatment. However, traditional PAs have shortcomings such as low water solubility, easy aggregation-induced fluorescence quenching and low target site accumulation efficiency, which severely limit clinical anticancer applications. Naturally derived polysaccharides have attracted great attention in the scientific community in nano-drug delivery systems (NDDS) due to their abundant resources, biocompatibility, targeting ability, bioactivity and so on, which is expected to assist PAs to play a synergistic effect. This article reviews the recent progress of polysaccharides in the field of cancer phototherapy, including the advantages of polysaccharides as nanocarrier materials to deliver PAs; the main mechanism for the preparation of PAs-loaded polysaccharides nanoformulation; construction of polysaccharides-based NDDS for delivery of PAs and its functional modification strategy, hoping to further improve the therapeutic effect of phototherapy against cancer.